2014
DOI: 10.1002/ana.24222
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cerebral gray matter and altered white matter in boys with Duchenne muscular dystrophy

Abstract: Both gray and white matter is affected in boys with DMD at a whole brain level. Differences between the DMD_Dp140(-) subgroup and controls indicate an important role for the Dp140 dystrophin isoform in cerebral development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
118
2
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(146 citation statements)
references
References 41 publications
10
118
2
9
Order By: Relevance
“…Further, reduced cerebral blood flow [27] and a global reduction in cerebral gray matter [36] has been reported in boys with DMD.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Further, reduced cerebral blood flow [27] and a global reduction in cerebral gray matter [36] has been reported in boys with DMD.…”
Section: Discussionmentioning
confidence: 89%
“…Fourteen of the patients had deletion mutations between exons 45 and 48, which put them at risk of being deficient in the Dp140 isoform localized to the central nervous system. This has been associated with changes in CBF and cognitive deficits [5,27]. The design was a randomized double-blind, placebo-controlled, crossover study of two 4-week treatments with either placebo (lactose monohydrate oral in gelatin capsules, 3 times daily) or sildenafil 20 mg [Revatio in gelatin capsules (Pfizer, New York, NY, USA), p.o., 3 times daily], with the treatments separated by a washout period of 2 weeks.…”
Section: Subjectsmentioning
confidence: 99%
“…Structural abnormalities in the brain have been recently described: changes in the cerebral grey matter volume and white matter microstructure in males with DMD have been described using quantitative magnetic resonance imaging. 35 Previous studies using magnetic resonance spectroscopy have indicated altered phosphorus metabolite ratios in the cerebral cortex of 19 males with DMD. 36 In an animal model, disrupted cerebral diffusivity was demonstrated to be associated with lack of dystrophin.…”
Section: Discussionmentioning
confidence: 98%
“…Secondly, since dystrophin mainly exists in the cerebral cortex, hippocampus, and cerebellar neurons, its absence may result in changes in WM tracts connected to homologous brain gray matter (GM). Doorenweerd et al using voxel-based morphometry found that DMD patients have a significantly smaller occipital cortex and significantly lower WM FA in the occipital lobe (37). Thirdly, during neural development, dystrophin is expressed within the neural tube and selected areas of the embryonic and postnatal neuraxis, and may regulate distinct © Annals of Translational Medicine.…”
Section: Discussionmentioning
confidence: 99%